FAKTOR FAKTOR YANG MEMPENGARUHI IMPOR BERAS DI INDONESIA (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2020)
Muhammad Ramadhani, 2019 ‘’Factors to affect the import of rice in Indonesia’’ guided by Jiuhardi and Erwin Kurniawan A.This research aims to determine the effect of rice production, total population and local rice prices on the import of rice in Indonesia.This research uses secondary data obtained from the Central Statistics Agency (BPS), the Ministry of Agriculture and Food Security (Kementan), and the General Company of Logistics Affairs (Perum Bulog).The analytical techniques used are multiple linear regression analyses.The results showed that rice production was affects negative and insignificant the import of rice in Indonesia. total population was affects positive and significant the import of rice in Indonesia. local rice prices was affects positive and significant the import of rice in Indonesia.